Back to the future? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The spotlight should soon shine on organic agriculture, according to its backers. They believe that the future of food consumption and agricultural practices is organic. True, consumers in industrialised countries have learned to their cost that for...